2009
DOI: 10.1093/nar/gkp681
|View full text |Cite
|
Sign up to set email alerts
|

MBNL and CELF proteins regulate alternative splicing of the skeletal muscle chloride channel CLCN1

Abstract: The expression and function of the skeletal muscle chloride channel CLCN1/ClC-1 is regulated by alternative splicing. Inclusion of the CLCN1 exon 7A is aberrantly elevated in myotonic dystrophy (DM), a genetic disorder caused by the expansion of a CTG or CCTG repeat. Increased exon 7A inclusion leads to a reduction in CLCN1 function, which can be causative of myotonia. Two RNA-binding protein families—muscleblind-like (MBNL) and CUG-BP and ETR-3-like factor (CELF) proteins—are thought to mediate the splicing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 56 publications
7
76
2
Order By: Relevance
“…S5C). Muscleblind-like protein 1 (MBNL1) is highly expressed in cardiac and skeletal muscles (52) and is a known regulator of mRNA splicing in these tissues (53,54). Intron retention has emerged as a widespread mechanism to regulate gene expression in different cell and tissue types as well as during stem cell differentiation (42,55,56).…”
Section: Discussionmentioning
confidence: 99%
“…S5C). Muscleblind-like protein 1 (MBNL1) is highly expressed in cardiac and skeletal muscles (52) and is a known regulator of mRNA splicing in these tissues (53,54). Intron retention has emerged as a widespread mechanism to regulate gene expression in different cell and tissue types as well as during stem cell differentiation (42,55,56).…”
Section: Discussionmentioning
confidence: 99%
“…In intron 4 of the MBNL1 pre-mRNA, we observed that MBNL1 regulates exon 5 exclusion by binding a response element located within an AGEZ just downstream of a distant branch point and PY tract. In the CLCN1 pre-mRNA, MBNL1 represses exon 7A inclusion by binding the 5Ј-end of exon 7A (which contains an exonic splicing enhancer) and flanking intronic regions (42). Previously, we showed that MBNL1 and U2AF65 compete for binding at the 3Ј-end of intron 4 of the TNNT2 pre-mRNA to regulate exon 5.…”
Section: Polypyrimidine Tract-binding Protein 1 (Ptb1) and Mbnl1 Negamentioning
confidence: 99%
“…The muscleblind splicing regulatory factor Mbnl1 has been directly implicated in the causation of DM1 because it binds CUG repeats, colocalizes with CUG-repeat RNA foci and regulates the alternative splicing of genes mis-spliced in DM1 patients (Fardaei et al, 2002;Ho et al, 2004;Kino et al, 2009;Mankodi et al, 2001;Osborne et al, 2009). Altered mRNA splicing has been reported in more than 20 genes in DM1 patients (Kalsotra et al, 2008;Lin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%